PENERAPAN PSAK 72 TERKAIT PENDAPATAN DARI KONTRAK DENGAN PELANGGAN PADA PT TELEKOMUNIKASI INDONESIA TBK - Hayati Puspamurti; Amrie Firmansyah (INDONESIAN JOURNAL OF ACCOUNTING AND GOVERNANCE, 2020)
This study aims to review the application of PSAK 72 regarding Revenue from Contracts with Customers at PT Telkom Tbk. This study employs qualitative methods with a literature study approach, content analysis, and interviews. Interviews were conducted with two informants consisting of academic and PT Telkom internal party. It was conducted in May 2020. This study concluded that PSAK 72 (2017) by PT Telkom Tbk was effective since January 1, 2020, and is not an early application in Indonesia because, in 2018 and 2019, PT Telkom Tbk used PSAK 23 (2014). The implementation of IFRS 15 (2014) by PT Telkom Tbk since 2018 has not made the financial reports submitted to the IDX early-adopting PSAK 72 (2017). PT Telkom Tbk has made preparations related to the implementation of PSAK 72 (2017) since the end of 2016.